2013
DOI: 10.1007/s13197-013-1147-z
|View full text |Cite
|
Sign up to set email alerts
|

Determination of fat, protein and moisture in ricotta cheese by near infrared spectroscopy and multivariate calibration

Abstract: Near-infrared reflectance spectroscopy (NIRS) with partial least squares regression (PLSR) was used to determine levels of fat, protein and moisture in ricotta cheese without complex sample preparation. Spectra of 19 conventional and low-fat ricotta samples from different manufacturers were collected in duplicate, with 33 of the 38 spectra used as a calibration set and the remaining 5 spectra used as an external validation set. The best results were obtained by processing the spectral region between 1,100 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Among them, we included some fruits that typically grow in the Sicilian area and demonstrated important health benefits, such as red oranges (Grosso et al 2013), prickly pears (Feugang et al 2006), pomegranates (Sreekumar et al 2014), artichoke (Rondanelli et al 2013) and some characteristic foods that may have peculiar nutritional profile [i.e. ''ricotta'' whey cheese have less fats than more common cheeses (Madalozzo et al 2015)]. We also included several varieties of fisheries and nuts, which may be highly characterized in the Sicilian area and have been demonstrated to exert peculiar effects on health (Gil & Gil 2015;Grosso & Estruch 2016), and distinguished between extra virgin olive oil and other oils (Sacchi et al 2014).…”
Section: Food Frequency Questionnairementioning
confidence: 99%
“…Among them, we included some fruits that typically grow in the Sicilian area and demonstrated important health benefits, such as red oranges (Grosso et al 2013), prickly pears (Feugang et al 2006), pomegranates (Sreekumar et al 2014), artichoke (Rondanelli et al 2013) and some characteristic foods that may have peculiar nutritional profile [i.e. ''ricotta'' whey cheese have less fats than more common cheeses (Madalozzo et al 2015)]. We also included several varieties of fisheries and nuts, which may be highly characterized in the Sicilian area and have been demonstrated to exert peculiar effects on health (Gil & Gil 2015;Grosso & Estruch 2016), and distinguished between extra virgin olive oil and other oils (Sacchi et al 2014).…”
Section: Food Frequency Questionnairementioning
confidence: 99%
“…For construction of the model for moisture analysis by NIRS, the R 2 values for calibration and validation were considered low in all treatments. Madalozzo, Sauer & Nagata (2015), in their study on the physicochemical characterization of ricotta cheese also using NIRS methodology, verified a correlation coefficient of 0.851% for calibration and a coefficient of 0.757% for validation. They also stated that there was a lower capacity prediction model for moisture determination as verified in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…Examining artisanal and industrial Ricotta samples Mattera et al (35) noticed that industrial Ricotta showed a greater homogeneity in view of their chemical composition. Lack of uniformity with greater coefficients of variation found for fat (48.35%) and protein (23.61%) was determined in a research done by Madalozzo et al (36). Casti et al (30) indicated the role of raw material quality and contrary to our results they obtained higher values for total solids (42.12%), fat (19.55%), protein (14.84%) and salt (3.42%) for Ricotta produced from whey from sheep milk cheeses.…”
Section: Discussionmentioning
confidence: 91%